Pengaruh Penggunaan TikTok terhadap Akhlak Peserta Didik Kelas VII SMP Negeri 29 Padang - Pratiwi, Astri Ayu Sintya; Wirdati, Wirdati (TSAQOFAH, 2025)
This study is motivated by the decline in students’ moral behavior, which is suspected to be influenced by the use of the TikTok application. The aim of the study is to determine the level of TikTok usage, the moral character of students, and the influence of TikTok usage on the moral character of seventh-grade students at SMP Negeri 29 Padang. This research uses a quantitative method with a correlational research design. The population consists of 306 students, with a sample of 75 students selected through simple random sampling. Data were collected using a questionnaire and analyzed with SPSS 25 software. Descriptive test results indicate a relatively high tendency of TikTok use among students. Correlation analysis shows a strong and significant relationship between TikTok usage and students’ moral character, with a correlation coefficient of 0.612 and a significance value of < 0.001, which is less than 0.05. This indicates that TikTok usage has a significant effect on students’ moral character, contributing 37.5%, while the remaining 62.5% is influenced by other factors not examined in this study. These findings highlight the need for supervision and education regarding social media use among students to prevent negative impacts on their character development.